Too Much of a Good Thing? : Prudent Management of Inflows under Economic Citizenship Programs - Xu, Xin (IMF Working Papers; Working Paper ;, 2015)
Economic Citizenship Programs (ECPs) have recently been proliferating, with large and potentially volatile inflows of investment and fiscal revenues generating significant benefits for small economies, but also posing substantial challenges. This paper discusses recent developments and implications of such programs for fiscal discipline and the real economy, including risks to macroeconomic and financial stability, with a focus on small state economies. It discusses the prudent management of these programs, overviews strategies to minimize risks to various sectors, and addresses potential governance and integrity challenges. The paper proposes a framework for managing inflows and savings from ECPs to contain macroeconomic risks, and it recommends the establishment of a sovereign wealth fund (SWF) where such revenues are large and persistent.